THE RELATIVE QUANTUM EFFICIENCY OF ANTHRACENESOLUTION AS A FUNCTION OF LIGHT EXPOSURE DURATION - Al-Tememee, Nathera; Al- Ani, Selwa (Iraqi Journal of Science, 2025)
In this paper the effect of light exposure duration on Anthracene solution inchloroform is studied. It is found that: the Anthracene solution change its color whenit is exposed to light, and that its relative quantum efficiency, Φ, decreases as thelight exposure duration, t, increases and this govern by following empiricalequation:-